Construction of High-Speed Tracks - Stanislav Hodas (Communications - Scientific letters of the University of Zilina, 2011)
The current situation and conditions of construction of high speed tracks (HST) in the Slovak Republic and the comparison with the situation abroad. The speed of train sets and the track quality for high speed trains. The dynamics of railway running. The speeds of the HST trains are limited by the respective track state. The tilting train set wagons - increasing the new levels of speeds in railway curves. The time comparison of the high speed trains to air and road transport “from city centre to city centre”. The required conditions and parameters of construction of high speed tracks up to Vmax 200–240 km.h1 within the track modernizations.